Pentingnya Pendidikan Anti Korupsi Dalam Dunia Pendidikan Terkhusus Pada Perguruan Tinggi Guna Pencegahan Korupsi - Anggun Novelin Butarbutar (Program Studi PPKn Universitas Pendidikan Ganesha, 2022)
This study aims to find out how important anti-corruption education is in the world of education, especially in tertiary institutions for preventing corruption. The research method used in this study is a normative research method by conducting and searching for data through library research or documents studies. Corruption is a behavior that is carried out with the intent and purpose of enriching oneself. There are 2 factors for corruption, namely internal factors and external factors. The perpetrators of corruption are people who have power and authority and do not have responsibility. The role of tertiary institution in helping prevent corruption is by conducting anti-corruption counseling to student, providing anti-corruption education courses on campus, and inviting and directing students to go down to the social strata to assist law enforcement in eradicating corruption in Indonesia.